2008
DOI: 10.1175/2008jcli2163.1
|View full text |Cite
|
Sign up to set email alerts
|

Global Climate Model Performance over Alaska and Greenland

Abstract: The performance of a set of 15 global climate models used in the Coupled Model Intercomparison Project is evaluated for Alaska and Greenland, and compared with the performance over broader pan-Arctic and Northern Hemisphere extratropical domains. Root-mean-square errors relative to the 1958–2000 climatology of the 40-yr ECMWF Re-Analysis (ERA-40) are summed over the seasonal cycles of three variables: surface air temperature, precipitation, and sea level pressure. The specific models that perform best over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
165
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(173 citation statements)
references
References 13 publications
8
165
0
Order By: Relevance
“…As in previous studies (Walsh et al 2008;Smith and Chandler 2010), our results show that models with better reproducibility in the present-day precipitation predict a more consistent change over the tropics (30 S-30 N). As argued by Knutti (2010), this is helpful information for decreasing the spread of future changes.…”
Section: Summary and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As in previous studies (Walsh et al 2008;Smith and Chandler 2010), our results show that models with better reproducibility in the present-day precipitation predict a more consistent change over the tropics (30 S-30 N). As argued by Knutti (2010), this is helpful information for decreasing the spread of future changes.…”
Section: Summary and Discussionsupporting
confidence: 88%
“…Evaluating the credibility of future projections is becoming an increasingly important issue. Some studies constrain projections using observations, suggesting that the models performing well in a present-day climate predict more converged future changes (Walsh et al 2008;Smith and Chandler 2010;Shiogama et al 2011). Abe et al (2009) show that the similarities observed in the precipitation distribution among the models in the present-day climate is significantly correlated with the similarities observed in the projected precipitation change over the tropics (15 S-15 N).…”
Section: Introductionmentioning
confidence: 98%
“…Change will also differ depending on the local trends in climate. Although trees in continental parts of the southern border of boreal forest may experience increased drought stress, precipitation will likely increase in more maritime southern boreal zones (e.g., in Scandinavia or Labrador) (37), perhaps leading to an expansion of forest (38,39). The scenarios of change are perhaps most difficult to infer at the northern end of the boreal range.…”
Section: Discussionmentioning
confidence: 99%
“…The CMIP3 ensemble is often used to quantify climate uncertainty, and based on the assumption that this ensemble would be used for future sensitivity analysis, it is reasonable to use a model that represents the ensemble mean. HadCM3 has also been shown to be one of the best performers when compared against absolute and bias corrected observations of surface parameters [Franco et al, 2011;Walsh et al, 2008].…”
Section: Climate Datamentioning
confidence: 99%